Policy on Termination of New Land Permits: Adverse Impact on Economic Development in Meranti, Riau - Nirwana, Latansa Kunta; Salim, M. Nazir; Retno Dewi, Asih (Marcapada: Jurnal Kebijakan Pertanahan, 2025)
Indonesia is developing by facilitating the investment climate. The Regulation in Lieu of the Job Creation Law No. 2 of 2022 shows the government's seriousness in the Ease of Doing Business. One sector with significant development potential is the land sector, which can utilise the economic value of land certificates to provide access to community capital. However, on the other hand, the policy of stopping the granting of new permits on peatlands has caused a policy conflict that has an impact on community economic access. With a field study and spatial analysis approach, this study traces data by conducting observations and in-depth interviews with various sources who understand the issue of the policy of stopping new permits related to peatlands in the Meranti Islands Regency (Meranti). The purpose of this study was to determine the condition of land and spatial planning in Meranti and its impact on the economic conditions of the community. The results of the study found that the implementation of the PIPPIB policy in Meranti, which is still indicative, is very powerful in stopping new permits. The PIPPIB policy has an impact on community land that has been certified so that derivative services cannot be implemented. This condition has caused a decline in the community's economy and increased the number of poor people in Meranti. In the end, the PIPPIB policy that is not participatory and does not care about the conditions of the Meranti community becomes a non-strategic policy strategy and causes misery to the community.